Groundwater Conservation Strategy Based on Water Balance at Muarabungo Groundwater Basin, Indonesia - Mochamad Nursiyam Barkah; Fauziyah Hani; Bombom Rachmat Suganda; Munib Ikhwatun Iman; Cecep Yandri Sunarie; Mohamad Sapari Dwi Hadian (Journal of Geoscience, Engineering, Environment, and Technology, 2021)
Muarabungo Groundwater Basin,is locateed in Jambi and West Sumatra Province. Based on the four rainfall stations in Muaratebo, Dusun Rantau Pandan, Sungai Bengkal and Komplek Pengairan PU Station recorded in 2008 to 2011, the precipitation (ppt) in study area is 1799.09 mm/year. Value of evapotranspiration (Evpt) in the study area is equal to 1261.26 mm / year (70.1%). Groundwater Basin of Muarabungo has an infiltration debit of 2,516,791,750 m3 / year and run-off debit (Ro) of 798 042 638 m3 / year. Rock composer in the Muarabungo Groundwater Basin are dominated by Alluvium Deposition, Quaternary rocks, and also the surrounding areas are composed by igneous and metamorphic rocks. Aquifer with a good productvity can be found on Alluvium and sedimentary rocks such as tuff sandy, whereas region without exploitable groundwater are composed by igneous rocks and metamorphic rocks. Based on groundwater quality, Groundwater Basin is divided into 13 facies, namely Ca; Cl, ​​Mg; Cl, ​​Na + K, Cl, Ca; HCO3, Mg; HCO3, Na + K; HCO3, Ca; No. dominant type, Mg; Nodominan type, Na + K; No. dominant type, No. dominant type; Cl, ​​No. dominant type; HCO3, Nodominan type; SO4, and No. dominant type; No. dominant type. The result of water balance measurement in research area is used to show the areas for crisis and secure area. The water balance calculation and determining recharge and discharge areas are needed for developing conservation strategy.